إشكالية الأمومة في الخطاب النسوي الغربي - بن غنيسة، نصر الدين; بن غنيسة، إيمان (جامعة باجي مختار-عنابة - كلية الآداب والعلوم الإنسانية - مخبر الأدب العام والمقارن, 2020)
All along history of feminist movement, maternity constituted one of the most complex problematics about which feminist speech developed two contradictory visions: one accuses the patriarchal power of reducing to its biological dimension of maternity assigning to the procreation a function purely cultural namely the preservation pf human race. In the opposite ,another vision puts the maternity at the heart of political stake ,by betting on it as being a power ,this vision aspire to reconstruct society at its image. Thus, our communication is about re-reading history of feminism through the prism of maternity attempting to spot ideological articulations and positions statements towards maternity that has marked different intellectual courses of feminist movement .The starting point refers to the first wave of the movement at the beginning of the 20th century where maternity was perceived as being at the spear head of the combat for woman .This speech has been taken by the third wave called Differentialist Feminism (kristeva ) during the eighties by appropriating biological heritages of body . The theory tries to free the woman from predefined roles by the society and to offer the possibility of living maternity as a function that contribute to the production of citizens and that against the conception that see in the woman’s body as simple cultural construction .It’s based on this conception that materialist flow (Monique witting ) of feminist movement of the sixties could develop its theory of maternity as being a pure production of the patriarchal culture depriving the woman of her freedom to be or to not to be a mother namely from her free choice to define her own sexual or asexual identity.
لقد شكلت تيمة الأمومة إحدى أهم القضايا التي وقف أمامها الخطاب النسوي في مفترق الطرق؛ بحيث تنازعته رؤيتان متناقضتان، رؤية تدين اختزال هوية المرأة في خاصيتها البيولوجية المتمثلة في الإنجاب الذي تحول إلى قيمة ثقافية عنوانها حفظ النوع البشري، الأمر الذي تلقفه الفكر البطريركي ليعزز هيمنته على المرأة، وأخرى تراهن على الانتصار لقيمة الأمومة كسلطة مضادة. يسعى المقال إلى الوقوف على أهم التمفصلات الأيديولوجية التي حكمت المسارات الفكرية للحركة النسوية في تعاطيها مع إشكالية الأمومة، بدءا من الموجة الأولى من الحركة النسوية، في بدايات القرن العشرين، التي أولت قيمة عظمى للأمومة في إطار النضال من أجل حصول المرأة على حقوقها المدنية. جاءت الموجة الثالثة من الحركة في ثمانينيات هذا القرن، عرفت بالنسوية التفاضلية (كريستيفا) لتعضد هذه الرؤية، إذ رأت أن الاعتراف بالأمومة كمعطى بيولوجي من شأنه أن يعيد صياغة علاقات المجتمع وفق قيم الأمومة. وفي مقابل ذلك نحن مدعوون للوقوف على المنظور النسوي للموجة الثانية من الحركة النسوية (مونيك وتيك) في سبعينيات القرن العشرين، والتي بناء على ملمحها المادي دعت إلى إلغاء الحتمية البيولوجية للأمومة بعدها بنية ثقافية من إنتاج المجتمع البطريركي، وجعلها خيارا شخصيا تحدد من خلاله المرأة هويتها اللاجنسية.
Keywords: المرأة -- الأمومة -- الخطاب النسوي -- الحركة النسوية -- المجتمع البطريركي -- الفكر الغربي